Primary ovarian leiomyoma - Shweta Raje; Sharda Arvind; Gayatri Rao; Latika Chawla (Wolters Kluwer Medknow Publications, 2020)
Primary ovarian leiomyoma is an extremely rare form of extrauterine leiomyomas. The incidence of primary ovarian leiomyoma is 0.5%-1% of all benign ovarian smooth muscle tumors. We present a case of primary ovarian leiomyoma managed laparoscopically with ovarian preservation.